Assessment of acceptability of the COVID-19 vaccine based on the health belief model among Malaysians-A qualitative approach - Mohd Dzulkhairi Mohd Rani; Nurul Azmawati Mohamed; Hana Maizuliana Solehan; Muslimah Ithnin; Abd Rasyid Ariffien; Ilina Isahak (Public Library of Science, 2024)
Indexed by WOS/SCOPUS/ERA